FREQUENCY OF PARASITIC INFESTATION IN FAECAL SPECIMENS - Ali, Arif Maqsood; Masud, Tariq; Arif, Shazia (Journal of Ayub Medical College Abbottabad, 2014)
Background: Parasitic infestation is very common in developing countries. Major factors of worm infestation are poor socio-economic status, large family size, low educational level, and poor hygiene and sanitation. These parasites lead to nutritional deficiencies and various diseases. A few studies have been carried out in Pakistan and this study tries to find out the frequency of parasitic infestation in our setup. Methods: A cross sectional study was carried out from December 2011 to February 2012 in Pakistan Aeronautical Complex (PAC) Hospital Kamra. Patients were asked to pass stool specimen in a universal container provided to them from the laboratory. Stool specimens were examined within half an hour by direct light microscopy of faecal smears in normal saline. The laboratory diagnosis was based on the demonstration of ova/cysts or trophozoites. Data were analysed by SPSS-10 and frequency of various parameters was determined. Results: A total of 543 faecal specimens were tested. Specimens found positive for ova/cysts were 295 (54%). Ascaris lumbricoides was the most frequent parasitic infestation in all faecal specimens followed by Taenia saginata. Thirty percent of food handlers were harbouring different parasitic infections. Diarrhoea/dysentery, medical examination of food handlers and for secondment abroad was the most frequent indication for faecal examination. Conclusion: High frequency of parasitic infestation in our set up especially of Taenia species requires measures to improve hygiene, water and sanitation. Meat and its products should be obtained from medically fit animals and meat cooked thoroughly before being consumed. Keywords: Anaemia, Ascaris lumbricoides, helminths, intestinal parasites, Taenia saginata